Growth and structural characterization of Sb2Se3 solar cells with vertical Sb4Se6 ribbon alignment by RF magnetron sputtering. (12th July 2021) - Spaggiari, Giulia; Pattini, Francesco; Bersani, Danilo; Calestani, Davide; De Iacovo, Andrea; Gilioli, Edmondo; Mezzadri, Francesco; Sala, Andrea; Trevisi, Giovanna; Rampino, Stefano
Abstract: Sb2 Se3, (ASe) thin-films were deposited as the absorber layers in photovoltaic solar cells using the radio frequency magnetron sputtering deposition technique. Starting from a binary target, high quality crystallization and good vertical alignment of Sb4 Se6 ribbons were attained at growth temperatures below 300 °C, and use of an additional selenization process was unnecessary for compensating Se loss. By the structural characterization of films grown on different substrates, a strong dependence of the ribbon orientation on the substrate type was verified. This study clearly confirms that the ribbon alignment is the key factor for enhancing the performance of Sb2 Se3 solar cells, in particular the short circuit current density ( J sc ). A photovoltaic efficiency of 0.24% and a J sc of 5 mA cm −2 were obtained by depositing ASe on Mo, in a CuInGaSe2 -like solar cell structure (Al:ZnO/ZnO/CdS/ASe/Mo/Glass), while the J sc was boosted up to 27 mA cm −2 when the ASe solar cells were fabricated in superstrate configuration with an Au/ASe/CdS/FTO architecture, leading to an efficiency of 2.36%.